2021
DOI: 10.3390/ijms22062888
|View full text |Cite
|
Sign up to set email alerts
|

Biflavonoid-Induced Disruption of Hydrogen Bonds Leads to Amyloid-β Disaggregation

Abstract: Deposition of amyloid β (Aβ) fibrils in the brain is a key pathologic hallmark of Alzheimer’s disease. A class of polyphenolic biflavonoids is known to have anti-amyloidogenic effects by inhibiting aggregation of Aβ and promoting disaggregation of Aβ fibrils. In the present study, we further sought to investigate the structural basis of the Aβ disaggregating activity of biflavonoids and their interactions at the atomic level. A thioflavin T (ThT) fluorescence assay revealed that amentoflavone-type biflavonoids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 57 publications
2
26
0
Order By: Relevance
“…Thus, the disruption of the Asp23-Lys28 salt bridge would lead to instability of the hydrogen bonds within the amino acid backbone that supports the fibrils and results in remodeling or disaggregation of the fibrils [85] . Using molecular docking (AutoDock Vina) and MD simulation with the disease-relevant Aβ fibril (PDB code: 2NAO), Windsor et al futher showed that the amentoflavone-type bioflavonoids disaggregate Aβ fibrils through the preferential binding to the N-terminal of the fibril via π-π interactions [89] , [90] . The aromatic rings of the compounds bind to the aromatic residues of the fibril and fit inside in the N-terminal pocket to stabilize the biflavonoid-fibril complex.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the disruption of the Asp23-Lys28 salt bridge would lead to instability of the hydrogen bonds within the amino acid backbone that supports the fibrils and results in remodeling or disaggregation of the fibrils [85] . Using molecular docking (AutoDock Vina) and MD simulation with the disease-relevant Aβ fibril (PDB code: 2NAO), Windsor et al futher showed that the amentoflavone-type bioflavonoids disaggregate Aβ fibrils through the preferential binding to the N-terminal of the fibril via π-π interactions [89] , [90] . The aromatic rings of the compounds bind to the aromatic residues of the fibril and fit inside in the N-terminal pocket to stabilize the biflavonoid-fibril complex.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the hydrogen bond formation between the hydroxy groups at R2/R3 of the compound with the peptide backbone resulted in a large decrease in β sheet content of the fibril and altered the structural conformation of the Aβ fibril. Thus, resulting in the disaggregation of the fibril [90] . The mechanism of the amyloid disaggregation by the small compounds is schematically shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][18][19][20] For example, several computational and experimental observations have shown that polyphenolic plant compounds which occur naturally in fruit, vegetables, chocolate, and tea are capable of inhibiting IDP aggregation. [12][13][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Finding aggregation inhibitors and direct targeting of monomeric IDPs via small molecules is a very active area of research and a wide variety of computational techniques have been applied, yet there are many inherent difficulties. 12-14, 27, 35-41 For example, most docking algorithms employ the flexible ligand and rigid receptor paradigm [42][43][44] but IDPs display high conformational heterogeneity, and ligand binding causes large structural changes in the IDP conformations.…”
Section: Introductionmentioning
confidence: 99%
“…Biflavonoids are flavonoid dimers consisting of two identical or non-identical flavonoid/flavone units linked by a C-C bond [25]. Biflavonoids have been reported to have anti-amyloidogenic effects by inhibiting aggregation of Aβ plaques and promoting the disaggregation of Aβ fibrils; this effect makes biflavonoids lead compounds in the treatment of Alzheimer's disease [26]. The preparation of biflavonoids using metal-catalyzed cross-coupling reactions has been previously reported in the literature.…”
Section: Introductionmentioning
confidence: 99%